Polymorphisms in WNT6 and WNT10A and colorectal adenoma risk - Galbraith, Rachel L.; Poole, Elizabeth M.; Duggan, David; Muehling, Jill; Hsu, Li; Makar, Karen; Xiao, Liren; Potter, John D.; Ulrich, Cornelia (Nutrition and cancer, 2011)
The WNT/β-catenin signaling pathway upregulates transcription of genes involved in cell proliferation and cancer progression; it has been implicated in colorectal adenoma formation. To date, no studies have examined polymorphisms in WNT genes or WNT gene-environment interactions in relation to adenoma risk. Within a colonoscopy-based case-control study of 628 adenoma cases and 516 polyp-free controls, we analyzed two tagSNPs in WNT6 (rs6747776 G > C, rs6754599 G > C) and WNT10A (rs7349332 G > A, rs10177996 A > G). The WNT6 rs6747776 homozygous minor allele (CC) was associated with increased risk of colorectal adenoma (OR = 2.75, 95% CI: 1.03-7.31). We observed a statistically significant interaction between WNT6 rs6747776 and the proportion of calories from total fat (P-int = 0.02), where the highest risk was observed among those with minor alleles and lowest fat intake. We also detected a marginally significant (0.05 < P ≤ 0.10) interaction with fish intake (P-int = 0.09). Additionally, a marginally significant interaction was observed between proportion of calories from saturated fat and the WNT10A rs7349332 polymorphism. Our results suggest that genetic variability in the WNT pathway may play a role in colorectal adenoma formation or may partly mediate the increased risk of colorectal cancer associated with fat intake.
Gesehen am 13.07.2023
Veröffentlicht in der endgültigen redaktionellen Form
Angabe zum PDF: Autorenmanuskript: verfügbar in PMC 2015 Mai 13, 13 Seiten